World E-Parliament Report 2012 - United Nations (United Nations, 2012)
The World e-Parliament Report 2012 presents the latest data on the use and availability of systems, applications, hardware and tools in parliaments all over the world. The findings presented in the report are based on the results of the Global Survey of ICT in Parliaments 2012 conducted by the Global Centre for ICT in Parliament between February and May 2012. Comparisons are offered in the 2008 and 2010 editions. The report provides readers with concrete examples of the adoption of ICT in the most significant areas of parliamentary business. The report is intended to be read in conjunction with the 2008 and 2010 reports.